A method for preparing a hydrogen sulfide gas-sensitive composite material and a hydrogen sulfide gas sensor
The CuO/ZnWO4 hydrogen sulfide gas-sensitive composite material was synthesized with copper acetate after hydrothermal reaction of zinc nitrate and sodium tungstate, which solved the problems of low response and poor selectivity of existing sensors, and achieved high sensitivity and fast response hydrogen sulfide gas detection.
Patent Information
- Application Number
- CN202311048463.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-08-21
AI Technical Summary
Existing semiconductor hydrogen sulfide gas sensitive sensors have low response, high response temperature and poor selectivity, making it difficult to effectively detect low-concentration hydrogen sulfide gas.
The hydrothermal reaction is carried out by zinc nitrate and sodium tungstate to generate zinc tungstate, and then hydrothermal reaction is carried out with copper acetate to prepare CuO/ZnWO4 hydrogen sulfide gas-sensitive composite material. The specific surface area is increased and p/n junction is formed by doping copper oxide. Improve sensitivity.
It realizes a hydrogen sulfide gas sensor with fast response, low response temperature and good selectivity, with high sensitivity, fast response/recovery time and good stability, and is suitable for the extensive detection of hydrogen sulfide gas.
Smart Images

Figure CN117069137B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen sulfide gas sensors, and more specifically, to a method for preparing a hydrogen sulfide gas-sensitive composite material and a hydrogen sulfide gas sensor. Background Art
[0002] Hydrogen sulfide is a toxic gas with a pungent odor. Low concentrations of hydrogen sulfide gas can damage the human eyes, nose, trachea and other organs. Inhaling high concentrations of hydrogen sulfide gas in a short period of time can cause olfactory paralysis and respiratory failure, and even cause death. On the one hand, hydrogen sulfide exists in sewers, toilets and the human body through the decomposition of organic matter by bacteria; on the other hand, hydrogen sulfide gas also exists in mines, such as oil mining, coal mining and other industrial production. Its corrosiveness and flammability will not only cause damage to equipment, but also cause poisoning of workers and threaten their lives and health. Therefore, the concentration of hydrogen sulfide gas needs to be detected in many industries.
[0003] At present, the most ideal method for gas detection is semiconductor gas sensors, because they have the advantages of low price, fast response, high sensitivity, easy electronic circuit technology integration, and easy use. The excellent performance of semiconductor gas sensors mainly depends on the performance of gas-sensitive materials. At present, the gas-sensitive materials of most semiconductor hydrogen sulfide gas sensors at home and abroad are based on SnO2 and ZnO as matrix materials, and copper ions are added to the gas-sensitive materials to improve the gas-sensitive performance of the components to H2S, and improve its sensitivity and selectivity. However, the current single metal oxide semiconductor gas sensors generally have the disadvantages of low response, high response temperature (200-400℃), and poor selectivity. Summary of the invention
[0004] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a hydrogen sulfide gas-sensitive composite material and a hydrogen sulfide gas sensor. The hydrogen sulfide gas-sensitive composite material and hydrogen sulfide gas sensor prepared by the preparation method of the present invention have the advantages of fast response, low response temperature, good selectivity, etc. At the same time, the preparation method is simple in process, strong in repeatability, and good in stability, which is conducive to the promotion and application of hydrogen sulfide gas sensors.
[0005] To this end, in the first aspect, an embodiment of the present invention provides a method for preparing a hydrogen sulfide gas-sensitive composite material, the preparation method comprising: dissolving a certain amount of zinc nitrate and sodium tungstate in deionized water in turn, and continuously stirring to form a uniform solution; transferring the above uniform solution to a reactor, performing a first hydrothermal reaction, and generating a primary reaction solution; after the first hydrothermal reaction is completed, the reactor is naturally cooled, the primary reaction solution is centrifuged and washed, and the obtained product is dried and annealed to obtain the product material zinc tungstate; taking a certain amount of zinc tungstate and ultrasonically stirring it to dissolve it in deionized water, adding a certain amount of copper acetate during the stirring process, and continuing to stir to form a mixed solution; transferring the above mixed solution to a reactor, performing a second hydrothermal reaction, and generating a secondary reaction solution; after the second hydrothermal reaction is completed, the reactor is naturally cooled, the secondary reaction solution is centrifuged and washed, and the obtained product is dried to obtain the hydrogen sulfide gas-sensitive composite material.
[0006] Preferably, the molar ratio of the zinc nitrate to the sodium tungstate added is 1:1.
[0007] Preferably, the first hydrothermal reaction temperature is 180° C., and the first hydrothermal reaction time is 12 h.
[0008] Preferably, the drying temperature is 50° C. and the drying time is 24 h; the annealing temperature is 600° C., the heating rate is 10° C. / min, and the annealing time is 2 h.
[0009] Preferably, the molar ratio of the added amount of the zinc tungstate to the added amount of the copper acetate is 1:1.
[0010] Preferably, the second hydrothermal reaction temperature is 180° C., and the second hydrothermal reaction time is 5 h.
[0011] Preferably, the drying temperature is 50° C. and the drying time is 24 h.
[0012] Preferably, the centrifugal washing step comprises: first centrifugal washing with alcohol for no less than 2 times, and then centrifugal washing with deionized water for no less than 1 time, the centrifugal speed is 8000 rpm, and the centrifugal time for each time is no less than 5 minutes.
[0013] In the second aspect, an embodiment of the present invention provides a method for preparing a hydrogen sulfide gas sensor, the preparation method comprising: grinding the hydrogen sulfide gas sensitive material prepared by the preparation method provided in the embodiment of the first aspect into a uniform fine powder in a mortar; adding a certain amount of anhydrous ethanol to the mortar and continuing to grind to obtain a mixed slurry; uniformly coating the mixed slurry on the surface of a ceramic tube so that the slurry completely covers the gold electrode on the surface of the ceramic tube, and obtaining the hydrogen sulfide gas sensor after the slurry is naturally dried.
[0014] Preferably, the grinding time is 5-10 min.
[0015] The preparation method of the hydrogen sulfide gas-sensitive composite material provided by the embodiment of the present invention utilizes zinc nitrate and sodium tungstate to carry out hydrothermal reaction during the preparation process, so that the prepared product zinc tungstate has high purity, and then utilizes zinc tungstate and copper acetate to carry out hydrothermal reaction to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material. The preparation method of the present invention increases the specific surface area of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material by doping copper oxide, providing more active sites for gas adsorption; at the same time, the formation of a large number of p / n junctions increases the resistance of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, thereby increasing the sensitivity of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material. Moreover, hydrogen sulfide gas can be quickly detected at room temperature and 100°C, and the range of hydrogen sulfide detected is wide, with the advantages of fast response, low response temperature and good selectivity. At the same time, the preparation method has simple process, strong repeatability, good stability, and is conducive to the promotion and application of hydrogen sulfide gas sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a flow chart of a method for preparing a hydrogen sulfide gas-sensitive composite material provided in an embodiment of the present invention.
[0017] Figure 2 A flow chart of a method for preparing a hydrogen sulfide gas sensor provided in an embodiment of the present invention.
[0018] Figure 3 1 is the XRD diagram of the hydrogen sulfide gas-sensitive composite material prepared in Examples 1-3 and Comparative Example 1 of the present invention.
[0019] FIG. 4 is a SEM image of the hydrogen sulfide gas-sensitive composite material prepared in Example 2 and Comparative Example 1 of the present invention.
[0020] Figure 5 The sensitivity dotted line graphs of the hydrogen sulfide gas sensors prepared by Comparative Example 1 and Examples 1 and 2 of the present invention to 25 ppm hydrogen sulfide gas at different temperatures.
[0021] Figure 6 The graph is a response curve of the hydrogen sulfide gas sensor prepared in Example 2 of the present invention to 25 ppm hydrogen sulfide gas at room temperature.
[0022] Figure 7 The graph is the response curve of the hydrogen sulfide gas sensor prepared in Example 1 of the present invention to 25 ppm hydrogen sulfide gas at 100°C.
[0023] Figure 8 The following are response curves of the hydrogen sulfide gas sensor prepared in Example 1 of the present invention to hydrogen sulfide gas of different concentrations at 100°C.
[0024] Fig. 9 5th response curve of the hydrogen sulfide gas sensor prepared by Example 1 of the present invention to 25 ppm hydrogen sulfide gas.
[0025] Fig.10 The selectivity of the hydrogen sulfide gas sensor prepared by Example 2 of the present invention to different gases. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0027] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not indicate the relationship between the various embodiments and / or settings discussed in itself. In addition, the examples of various specific processes and materials provided by the present invention, but those of ordinary skill in the art can be aware of the applicable fields of other processes and / or the use of other materials.
[0028] The embodiment of the present invention provides a method for preparing a hydrogen sulfide gas-sensitive composite material and a hydrogen sulfide gas sensor. The hydrogen sulfide gas-sensitive composite material of the present invention is a CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, which has the advantages of fast response, low response temperature, and good selectivity. The hydrogen sulfide gas sensor prepared by the hydrogen sulfide gas-sensitive composite material of the present invention has high sensitivity, fast response / recovery time, good stability, good selectivity, and good consistency and reproducibility.
[0029] like Figure 1 As shown, the first embodiment of the present invention provides a method for preparing a hydrogen sulfide gas-sensitive composite material, comprising the following steps:
[0030] Step S1: dissolving a certain amount of zinc nitrate and sodium tungstate in deionized water in sequence, and stirring continuously to form a uniform solution;
[0031] The molar ratio of the zinc nitrate (Zn(NO3)2·6H2O) to the sodium tungstate (Na2WO4·2H2O) is 1: 1. Furthermore, the zinc nitrate is added to deionized water, stirred, and completely dissolved before adding the sodium tungstate.
[0032] Step S2: transferring the uniform solution to a reaction vessel to perform a first hydrothermal reaction to generate a primary reaction solution;
[0033] Among them, the first hydrothermal reaction temperature is 180°C, and the first hydrothermal reaction time is 12h.
[0034] Step S3: After the first hydrothermal reaction is completed, the reactor is cooled naturally, the first reaction solution is centrifuged and washed, and the obtained product is dried and annealed to obtain the product material zinc tungstate;
[0035] Among them, the drying temperature is 50°C, and the drying time is 24h; the annealing temperature is 600°C, the heating rate is 10°C / min, and the annealing time is 2h; the centrifugal washing step includes: first centrifugal washing with alcohol, the number of times is not less than 2 times, and then centrifugal washing with deionized water, the number of times is not less than 1 time, the centrifugal speed is 8000 rpm, and the centrifugal time each time is not less than 5min.
[0036] Step S4: taking a certain amount of zinc tungstate and dissolving it in deionized water by ultrasonication and stirring, adding a certain amount of copper acetate during the stirring process, and continuing to stir to form a mixed solution;
[0037] Wherein, the molar ratio of the added amount of the zinc tungstate and the added amount of the copper acetate is 1:1.
[0038] Step S5: transferring the mixed solution to a reaction vessel to perform a second hydrothermal reaction to generate a secondary reaction solution;
[0039] Among them, the second hydrothermal reaction temperature is 180°C, and the second hydrothermal reaction time is 5h.
[0040] Step S6: After the second hydrothermal reaction is completed, the reactor is cooled naturally, the secondary reaction solution is centrifuged and washed, and the obtained product is dried to obtain the hydrogen sulfide gas-sensitive composite material.
[0041] Among them, the drying temperature is 50°C and the drying time is 24 hours; the centrifugal washing step includes: first centrifugal washing with alcohol for no less than 2 times, then centrifugal washing with deionized water for no less than 1 time, the centrifugal speed is 8000 rpm, and the centrifugal time for each time is no less than 5 minutes.
[0042] The preparation method of the hydrogen sulfide gas-sensitive composite material provided by the embodiment of the present invention uses zinc nitrate and sodium tungstate to carry out hydrothermal reaction during the preparation process, so that the prepared product zinc tungstate has high purity, and then uses zinc tungstate and copper acetate to hydrothermally react to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material. The preparation method of the present invention increases the specific surface area of the prepared CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material by doping copper oxide, providing more active sites for gas adsorption; at the same time, the formation of a large number of p / n junctions increases the resistance of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, increasing the sensitivity of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material. Moreover, hydrogen sulfide gas can be quickly detected at room temperature and 100°C, and the range of hydrogen sulfide detected is wide. Therefore, the hydrogen sulfide gas-sensitive composite material prepared by the preparation method provided by the embodiment of the present invention has the advantages of fast response, low response temperature and good selectivity. At the same time, the preparation method has a simple process, strong repeatability, good stability, and is conducive to the promotion and application of hydrogen sulfide gas sensors.
[0043] The second aspect of the present invention provides a method for preparing a hydrogen sulfide gas sensor, wherein the hydrogen sulfide gas sensor comprises a hydrogen sulfide gas-sensitive composite material prepared by the preparation method provided in the first aspect of the present invention. Figure 2 As shown, the preparation method of the hydrogen sulfide gas sensor includes the following steps:
[0044] Step S7: Grinding the hydrogen sulfide gas-sensitive material prepared in the first embodiment into uniform fine powder in a mortar;
[0045] The grinding time is 5-10 minutes.
[0046] Step S8: adding a certain amount of anhydrous ethanol to the mortar and continuing grinding to obtain a mixed slurry;
[0047] The grinding time is 5-10 minutes.
[0048] Step S9: uniformly coating the mixed slurry on the surface of the ceramic tube so that the slurry completely covers the gold electrode on the surface of the ceramic tube, and obtaining the hydrogen sulfide gas sensor after the slurry is naturally dried.
[0049] The hydrogen sulfide gas sensor prepared by the preparation method of the hydrogen sulfide gas sensor provided in the embodiment of the present invention has high sensitivity, fast response / recovery time, good stability, good selectivity, good consistency and reproducibility. When detecting hydrogen sulfide, the detection accuracy and precision are high, and significant economic benefits are achieved.
[0050] The specific process and effects of the preparation method of the hydrogen sulfide gas-sensitive composite material of the present invention are further described in detail below in conjunction with some specific embodiments, but are not limited to the protection scope of the present invention.
[0051] Example 1
[0052] This embodiment provides a method for preparing a hydrogen sulfide gas-sensitive composite material. The hydrogen sulfide gas-sensitive composite material prepared in this embodiment is a CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, which comprises the following steps:
[0053] Step S1: Add 2 mmol of zinc nitrate into 30 ml of deionized water, stir to dissolve, then add 2 mmol of sodium tungstate, and continue stirring to form a uniform solution.
[0054] Step S2: The uniform solution was transferred into a reaction vessel and maintained at 180° C. for 12 h.
[0055] Step S3: After the reaction is completed, the reactor is naturally cooled to room temperature and then centrifuged and washed. First, the reactor is centrifuged and washed twice with alcohol and then once with deionized water. The centrifugal speed is 8000 rpm and the centrifugal time is not less than 5 min each time. The obtained product is dried at 50°C in a blast drying oven for 24 h and finally annealed at 600°C in a muffle furnace at a heating rate of 10°C / min for 2 h to obtain the product material zinc tungstate.
[0056] Step S4: Take 200 mg of zinc tungstate, dissolve it in 30 ml of deionized water by ultrasonication for 30 minutes, and then stir it. During the stirring process, add 6.7 mg of copper acetate to form a light green mixed solution.
[0057] Step S5: The mixed solution was transferred to a reactor and maintained at 180° C. for 5 h.
[0058] Step S6: After the reaction is completed, the reactor is naturally cooled to room temperature, and the material is collected using the same centrifugal washing and drying parameters as in step S6 to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material.
[0059] Example 2
[0060] This embodiment provides a method for preparing a hydrogen sulfide gas-sensitive composite material. The hydrogen sulfide gas-sensitive composite material prepared in this embodiment is a CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, which comprises the following steps:
[0061] Step S1: Add 2 mmol of zinc nitrate into 30 ml of deionized water, stir to dissolve, then add 2 mmol of sodium tungstate, and continue stirring to form a uniform solution.
[0062] Step S2: The uniform solution was transferred into a reaction vessel and maintained at 180° C. for 12 h.
[0063] Step S3: After the reaction is completed, the reactor is naturally cooled to room temperature and then centrifuged and washed. First, the reactor is centrifuged and washed twice with alcohol and then once with deionized water. The centrifugal speed is 8000 rpm and the centrifugal time is not less than 5 min each time. The obtained product is dried at 50°C in a blast drying oven for 24 h and finally annealed at 600°C in a muffle furnace at a heating rate of 10°C / min for 2 h to obtain the product material zinc tungstate.
[0064] Step S4: Take 200 mg of zinc tungstate, dissolve it in 30 ml of deionized water by ultrasonication for 30 min, and then stir it. During the stirring process, add 14.2 mg of copper acetate to form a light green mixed solution.
[0065] Step S5: The mixed solution was transferred to a reactor and maintained at 180° C. for 5 h.
[0066] Step S6: After the reaction is completed, the reactor is naturally cooled to room temperature, and the material is collected using the same centrifugal washing and drying parameters as in step S3 to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material.
[0067] Example 3
[0068] This embodiment provides a method for preparing a hydrogen sulfide gas-sensitive composite material. The hydrogen sulfide gas-sensitive composite material prepared in this embodiment is a CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, which comprises the following steps:
[0069] Step S1: Add 2 mmol of zinc nitrate into 30 ml of deionized water, stir to dissolve, then add 2 mmol of sodium tungstate, and continue stirring to form a uniform solution.
[0070] Step S2: The uniform solution was transferred into a reaction vessel and maintained at 180° C. for 12 h.
[0071] Step S3: After the reaction is completed, the reactor is naturally cooled to room temperature and then centrifuged and washed. First, the reactor is centrifuged and washed twice with alcohol and then once with deionized water. The centrifugal speed is 8000 rpm and the centrifugal time is not less than 5 min each time. The obtained product is dried at 50°C in a blast drying oven for 24 h and finally annealed at 600°C in a muffle furnace at a heating rate of 10°C / min for 2 h to obtain the product material zinc tungstate.
[0072] Step S4: Take 200 mg of zinc tungstate, dissolve it in 30 ml of deionized water by ultrasonication for 30 min, and then stir. During the stirring process, add 22.5 mg of copper acetate to form a light green mixed solution.
[0073] Step S5: The mixed solution was transferred to a reactor and maintained at 180° C. for 5 h.
[0074] Step S6: After the reaction is completed, the reactor is naturally cooled to room temperature, and the material is collected using the same centrifugal washing and drying parameters as in step S3 to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material.
[0075] Comparative Example 1
[0076] This embodiment provides a method for preparing a hydrogen sulfide gas-sensitive composite material. The hydrogen sulfide gas-sensitive composite material prepared in this embodiment is a CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, which comprises the following steps:
[0077] Step S1: Add 2 mmol of zinc nitrate into 30 ml of deionized water, stir to dissolve, then add 2 mmol of sodium tungstate, and continue stirring to form a uniform solution.
[0078] Step S2: The uniform solution was transferred into a reaction vessel and maintained at 180° C. for 12 h.
[0079] Step S3: After the reaction is completed, the reactor is naturally cooled to room temperature and then centrifuged and washed. First, the reactor is centrifuged and washed twice with alcohol and then once with deionized water. The centrifugal speed is 8000 rpm and the centrifugal time is not less than 5 min each time. The obtained product is dried at 50°C in a blast drying oven for 24 h and finally annealed at 600°C in a muffle furnace at a heating rate of 10°C / min for 2 h to obtain the product material zinc tungstate.
[0080] Step S4: Take 200 mg of zinc tungstate, dissolve it in 30 ml of deionized water by ultrasonication for 30 min, and then stir. During the stirring process, do not add copper acetate.
[0081] Step S5: The mixed solution was transferred to a reactor and maintained at 180° C. for 5 h.
[0082] Step S6: After the reaction is completed, the reactor is naturally cooled to room temperature, and the material is collected using the same centrifugal washing and drying parameters as in step S3 to obtain the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material.
[0083] In order to verify the finished product quality of the hydrogen sulfide gas-sensitive composite material provided in the embodiment of the present invention, the hydrogen sulfide gas-sensitive composite materials of different embodiments were tested, and the hydrogen sulfide gas-sensitive composite materials prepared in the above-mentioned embodiments 1-3 and comparative example 1 were subjected to X-ray diffraction analysis. The XRD patterns of the hydrogen sulfide gas-sensitive composite materials prepared in embodiments 1-3 and comparative example 1 are as follows: Figure 3 The hydrogen sulfide gas-sensitive composite materials prepared in the above-mentioned Example 2 and Comparative Example 1 were subjected to SEM analysis. The SEM images of the hydrogen sulfide gas-sensitive composite materials prepared in Example 2 and Comparative Example 1 are shown in FIG4 , wherein Figure 4ais a SEM image of the hydrogen sulfide gas-sensitive composite material prepared in Comparative Example 1, Figure 4b This is a SEM image of the hydrogen sulfide gas-sensitive composite material prepared in Example 2.
[0084] from Figure 3 It can be seen that after combining with copper oxide, the X-ray diffraction peak is consistent with the ZnWO4 standard PDF card, and no extra diffraction peaks appear. The addition of copper oxide does not affect the diffraction peak of ZnWO4. The main reason is that the content of copper oxide is small, so it does not affect the diffraction peak of the main material. As can be seen from Figure 4, the hydrogen sulfide gas-sensitive composite materials obtained by the comparative example and the embodiment are all loose structures formed by the accumulation of particles, and the particle size distribution is relatively uniform. The particle size is basically distributed in 20-100nm, and there is no larger particle size. The average particle size of the hydrogen sulfide gas-sensitive composite material is slightly reduced after compounding calculated by XRD and SEM test results. The smaller the particle size, the larger the specific surface area, and the more active sites that can be provided, thereby increasing the sensitivity of the hydrogen sulfide gas-sensitive composite material.
[0085] The hydrogen sulfide gas-sensitive composite material obtained in Comparative Example 1 and Examples 1 and 2 is used to prepare a hydrogen sulfide gas sensor, and the specific steps are as follows: grind the hydrogen sulfide gas-sensitive composite material in a mortar for 5-10 minutes to grind the hydrogen sulfide gas-sensitive composite material into uniform fine powder. Then, a certain amount of anhydrous ethanol is added to the mortar and the grinding is continued for several minutes to make the hydrogen sulfide gas-sensitive composite material into a mixed slurry with moderate viscosity, and the mixed slurry is evenly coated on the surface of the ceramic tube welded on the base so that the slurry completely covers the gold electrode on the surface of the ceramic tube, and the hydrogen sulfide gas sensor is obtained after the slurry is naturally dried.
[0086] In order to verify the finished product quality of the hydrogen sulfide gas sensor prepared by the embodiment of the present invention, the hydrogen sulfide gas sensors prepared by different embodiments were tested (the following tests were all compared and detected using the WS-30A gas sensitive testing system of Zhengzhou Weisheng Electronic Technology Co., Ltd.), including the following test items and test methods.
[0087] (1) Sensitivity test
[0088] Figure 5 The sensitivity of the hydrogen sulfide gas sensor prepared by comparative example 1 and examples 1 and 2 of the present invention to 25 ppm hydrogen sulfide gas at different temperatures is shown in dotted line graphs. Figure 5It can be seen that the hydrogen sulfide gas sensor prepared by Example 2 exhibits the highest response of 665.7 at room temperature, and the sensitivity of the hydrogen sulfide gas sensor decreases sharply with the increase of temperature; the sensitivity of the hydrogen sulfide gas sensor prepared by Comparative Example 1 increases slightly with the increase of temperature, reaching 4.5 at 100°C, but is still lower than the sensitivity of Examples 1 and 2 at 100°C (13.5 / 21.5 respectively).
[0089] (2) Response / recovery time test at optimal operating temperature
[0090] Figure 6 The response curve of the hydrogen sulfide gas sensor prepared in Example 2 of the present invention to 25 ppm hydrogen sulfide gas at room temperature is shown in FIG. Figure 7 The response curve of the hydrogen sulfide gas sensor prepared in Example 1 of the present invention to 25 ppm hydrogen sulfide gas at 100°C is shown in FIG. Figure 6 It can be seen that the hydrogen sulfide gas sensor prepared in Example 2 exhibits a good response and response rate, with a response time of 78s, but its recovery is poor. In order to solve this defect, we use a method of applying a heating pulse voltage to heat the hydrogen sulfide gas-sensitive composite material to 300°C. Figure 6 It can be seen from the figure that the hydrogen sulfide gas-sensitive composite material has completed recovery at the moment of heating. Figure 7 It can be seen that the hydrogen sulfide gas sensor prepared in Example 1 exhibits balanced performance at a temperature of 100° C., with a response time and a recovery time of 80 s and 138 s, respectively.
[0091] (3) Tests on different gas concentrations
[0092] The hydrogen sulfide gas sensor prepared in Example 1 was tested at an operating temperature of 100° C. After the baseline was stable, hydrogen sulfide gas of different concentrations was introduced, the test chamber was opened, the baseline was restored to stability, and the gas sensitivity test was completed. Figure 8 The response curve of the hydrogen sulfide gas sensor prepared in Example 1 of the present invention to different concentrations of hydrogen sulfide gas at 100°C is shown in FIG. Figure 8 It can be seen that after combining with copper oxide, it still has a rapid response and recovery speed to low concentration hydrogen sulfide.
[0093] (4) Continuous response stability test
[0094] The hydrogen sulfide gas sensor prepared in Example 1 was tested at an operating temperature of 100° C. After the baseline was stable, 25 ppm of hydrogen sulfide gas was introduced for detection. The gas was filled and discharged five times continuously, and the test was completed. Fig. 9The five response curves of the hydrogen sulfide gas sensor prepared in Example 1 of the present invention to 25 ppm hydrogen sulfide gas are shown in FIG. Fig. 9 It can be seen that the response curve has no obvious attenuation over time and has good stability.
[0095] (5) Selective testing
[0096] The hydrogen sulfide gas sensor prepared in Example 2 was tested at a working temperature of 100° C. After the baseline was stable, 100 ppm of ammonia, ethylene glycol, methanol, and acetone were introduced for detection. Fig.10 In order to determine the selectivity of the hydrogen sulfide gas sensor prepared in Example 2 of the present invention to different gases, Fig.10 It can be seen that compared with the response to 25ppm hydrogen sulfide gas, the hydrogen sulfide gas sensor prepared by Example 2 of the present invention has extremely low response to several other gases, thereby proving that the CuO / ZnWO4 composite material prepared by the preparation method of the hydrogen sulfide gas-sensitive composite material provided by the embodiment of the present invention has good selectivity for hydrogen sulfide gas.
[0097] In summary, the preparation method of the present invention increases the specific surface area of the prepared CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material by doping copper oxide, providing more active sites for gas adsorption; at the same time, the formation of a large number of p / n junctions increases the resistance of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material, thereby increasing the sensitivity of the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material. It exhibits a higher response and a shorter response time at room temperature; at 100°C, it not only exhibits a good response, but also exhibits a shorter response time and good recovery. The hydrogen sulfide gas sensor prepared based on the CuO / ZnWO4 hydrogen sulfide gas-sensitive composite material provided by the embodiment of the present invention has high sensitivity, fast response / recovery time, good stability, good selectivity, and good consistency and reproducibility. When detecting hydrogen sulfide, the detection accuracy and precision are high, and it has significant economic benefits. At the same time, the preparation method has a simple process flow and is suitable for application in large-scale industrial production.
[0098] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0099] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a hydrogen sulfide gas-sensitive composite material, characterized in that: The preparation method comprises: Step S1: dissolving a certain amount of zinc nitrate and sodium tungstate in deionized water in sequence, and stirring continuously to form a uniform solution; Step S2: transferring the uniform solution to a reaction vessel to perform a first hydrothermal reaction to generate a primary reaction solution; Step S3: After the first hydrothermal reaction is completed, the reactor is cooled naturally, the first reaction solution is centrifuged and washed, and the obtained product is dried and annealed to obtain the product material zinc tungstate; Step S4: taking a certain amount of zinc tungstate and dissolving it in deionized water by ultrasonication and stirring, adding a certain amount of copper acetate during the stirring process, and continuing to stir to form a mixed solution; Step S5: transferring the mixed solution to a reaction vessel to perform a second hydrothermal reaction to generate a secondary reaction solution; Step S6: After the second hydrothermal reaction is completed, the reactor is cooled naturally, the secondary reaction solution is centrifuged and washed, and the obtained product is dried to obtain the hydrogen sulfide gas-sensitive composite material.
2. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In the step S1, the molar ratio of the added amount of zinc nitrate to that of sodium tungstate is 1:
1.
3. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In the step S2, the first hydrothermal reaction temperature is 180°C, and the first hydrothermal reaction time is 12 hours.
4. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In step S3, the drying temperature is 50°C and the drying time is 24 hours; the annealing temperature is 600°C, the heating rate is 10°C / min, and the annealing time is 2 hours.
5. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In the step S4, the molar ratio of the added amount of the zinc tungstate and the copper acetate is 1:
1.
6. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In the step S5, the second hydrothermal reaction temperature is 180° C., and the second hydrothermal reaction time is 5 hours.
7. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In step S6, the drying temperature is 50° C. and the drying time is 24 hours.
8. The method for preparing the hydrogen sulfide gas-sensitive composite material according to claim 1, characterized in that: In step S3 and step S6, the centrifugal washing step includes: first centrifugal washing with alcohol for no less than 2 times, and then centrifugal washing with deionized water for no less than 1 time, the centrifugal speed is 8000 rpm, and the centrifugal time for each time is no less than 5 minutes.
9. A method for preparing a hydrogen sulfide gas sensor, characterized in that: The preparation method comprises: Step S7: Grinding the hydrogen sulfide gas-sensitive material prepared by the method according to any one of claims 1 to 8 into uniform fine powder in a mortar; Step S8: adding a certain amount of anhydrous ethanol to the mortar and continuing grinding to obtain a mixed slurry; Step S9: uniformly coating the mixed slurry on the surface of the ceramic tube so that the slurry completely covers the gold electrode on the surface of the ceramic tube, and obtaining the hydrogen sulfide gas sensor after the slurry is naturally dried.
10. The method for preparing a hydrogen sulfide gas sensor according to claim 9, characterized in that: In step S7 and step S8, the grinding time is 5-10 min.
Citation Information
Patent Citations
Efficient photocatalytic hydrogen production catalytic system and preparation method thereof
CN112871209A
Hydrogen sulfide gas sensitive material and hydrogen sulfide gas sensor preparation method
CN115924959A